CORE STRENGTH TRAINING ON PHYSICAL CONDITIONING OF COLLEGE MALE SOCCER PLAYERS - He,Yulin (2022)
ABSTRACT Introduction: The concept of CORE emerged in mechanical-neurological studies of rehabilitation in the 80s, referring to the central muscles of the human trunk, including the lumbar-pelvis-abdominal-perineal-hip complex responsible for the body orthostatic stability and support. Strengthening the CORE has received increasing attention from sports medicine specialists after the 2000s, and strength training is the subject of recent research in competitive sports. However, there is still a lack of conceptual studies of protocols for training focused on soccer athletes. Objective: Verify a CORE strength training protocol based on the analysis of the CORE training concept, its main functions, and introductory practical examples. Methods: Literature data collection, experimental and statistical-mathematical methods, and theoretical analysis about CORE training focused on explosive strength performance in soccer players are used. The developed protocol experiments with 44 athletes, divided into experimental and control groups, by sex. Information is collected on goal shooting, 30-meter pass, balance, stability, and symmetry. Results: The group experienced better results in both sexes(P<0.05). Conclusion: The explosion strength indicators of the players were significantly improved. Whether male or female athletes, the higher the skill level, the stronger the CORE stability in players. Therefore, the CORE stability and strengthening in athletes promote a benefit in the technical level of soccer players. Evidence Level II; Therapeutic Studies - Investigating the result.